Cantinflas - Imperioli, Michael 1966-; Imperioli, Michael 1966-; Salas, Ilse; Méndez, Luis Gerardo; Garza, Gabriela de la; Jaenada, Óscar 1975- (Divisa Home Video, 2016)
From his humble origins on the small stage to the bright lights of Hollywood, the comedian Cantinflas became famous around the world, one joke at a time